Database on freshwater demand for electricity in Africa - International Water Management Institute (2024)
The database was developed as part of a research endeavor funded by the CGIAR Initiative on Foresight. This resulted in a paper analyzing freshwater demand for electricity in the year 2020. The paper is available from here: https://doi.org/10.1039/D4EW00246F.